Ketogenic diet: Predictors of seizure control. (3rd June 2017) - Agarwal, Nitin; Arkilo, Dimitrios; Farooq, Osman; Gillogly, Cynthia; Kavak, Katelyn S; Weinstock, Arie
Background: The ketogenic diet is an effective non-pharmacologic treatment for medically resistant epilepsy. The aim of this study was to identify any predictors that may influence the response of ketogenic diet. Methods: A retrospective chart review for all patients with medically resistant epilepsy was performed at a tertiary care epilepsy center from 1996 to 2012. Patient- and diet-related variables were evaluated with respect to seizure reduction at 1, 3, 6, 9 and 12-month intervals and divided into four possible outcome classes. Results: Sixty-three patients met inclusion. Thirty-seven (59%) reported >50% seizure reduction at 3 months with 44% and 37% patients benefiting at 6-month and 12-month follow up, respectively. A trend toward significant seizure improvement was noted in 48% patients with seizure onset >1 year at 12-month (p = 0.09) interval and in 62% patients with >10 seizure/day at 6-month interval (p = 0.054). An ordinal logistic regression showed later age of seizure to have higher odds of favorable response at 1-month (p = 0.005) and 3-month (p = 0.013) follow up. Patients with non-fasting diet induction were more likely to have a favorable outcome at 6 months (p = 0.008) as do females (p = 0.037) and those treated with higher fat ratio diet (p = 0.034). Conclusion: Our study reports the effectiveness of ketogenic diet in children with medically resistant epilepsy. Later age of seizure onset, female gender, higher ketogenic diet ratio and non-fasting induction were associated with better odds of improved seizure outcome. A larger cohort is required to confirm these findings.